1996
DOI: 10.1103/physreva.54.r5
|View full text |Cite
|
Sign up to set email alerts
|

Radiative lifetime of the2Pstate of lithium

Abstract: We determine the radial dipole moment between the 2S and 2 P states of atomic lithium by analyzing the long-range vibrational eigenenergies of the singly excited diatomic molecule. The result can be expressed in terms of the 2 P 1/2 radiative lifetime of 7 Li, which is found to be 27.102(2)(7) ns. This result agrees with most current atomic-structure calculations and resolves the long-standing disagreement with previous experiment. The current level of precision is sensitive to relativistic effects in the atom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

15
100
2

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(117 citation statements)
references
References 29 publications
15
100
2
Order By: Relevance
“…In accurate experiments McAlexander et al [26] reported a lifetime of the 2p state of 27.102(9) ns (an accuracy of 0.03%) and Martin et al [27] reported 27.13(2) ns. In our calculations we employ the more precise value from Ref.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In accurate experiments McAlexander et al [26] reported a lifetime of the 2p state of 27.102(9) ns (an accuracy of 0.03%) and Martin et al [27] reported 27.13(2) ns. In our calculations we employ the more precise value from Ref.…”
mentioning
confidence: 99%
“…In our calculations we employ the more precise value from Ref. [26]; in the subsequent error analysis we arbitrarily assigned an error bar of twice the quoted value of Ref. [26], so that the two experiments are consistent.…”
mentioning
confidence: 99%
“…This has allowed the determination of the lifetime of the 2p 1/2 state of lithium as 27.102(7) ns [3], the lifetime of the 3p 3/2 state of sodium as 16.230(16) ns [4], the lifetimes of the 4p 1/2 and 4p 3/2 states of potassium as 26.69(5)ns and 26.34(5) ns [5], the lifetimes of the 5p 1/2 and 5p 3/2 states of rubidium as 27.75(8) ns and 26.25 (8) ns [6], and the lifetimes of the 6p 1/2 and 6p 3/2 states of cesium as 34.88(2) ns and 30.462(3) ns [7]. (References to other experimental determinations of lifetimes, some of which are of higher accuracy, can be found in the above references.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, a precise τ value was obtained using a pure long-range expansion of the 0 − g (s + p 3/2 ) potential curve of dialkalis [35,36,37,38].…”
Section: Introductionmentioning
confidence: 99%